The Elimination of Illegal Waste in Hungary: New System of Sanctions and the First Results - Anita Boros; Gergely Zoltán Macher; András Torma (Chemical Engineering Transactions)
Illegal dumping is a persistent environmental challenge, with limited comprehensive data collection practices across EU Member States, leading to a lack of comparative databases on this issue. This paper addresses the problem by focusing on illegal dumping in Hungary and examining the development of a digital model for monitoring these activities, along with the characteristics and sanctions related to illegal dumping. By exploring waste management practices in the Visegrad Group Member States, this paper highlights the absence of systematic data collection and presents Hungary as a case example where citizens reported over 22,000 cases of illegal dumping in just six months via the WasteRadar application. The research findings underscore Hungary’s recent reforms, which introduced a nationwide database for tracking illegal dumping and imposed stricter sanctions aimed at mitigating the adverse environmental impacts of such activities. These actions signify important strides in addressing illegal dumping and improving environmental governance. This paper highlights the main characteristics of the reform of the Hungarian regulation, such as the advantages of the introduced method, such as establishing a country-wide database on illegal dumping and introducing significantly stricter sanctions on this activity to reduce the harmful environmental effects.